Education Management System Approach - Amiruddin Amiruddin; Tulus Abdul Wahid; Togu Yunus Hidayatullah; Wardani Wardani; Yuli Amelia (Edumaspul: Jurnal Pendidikan, 2022)
Systems approach is needed in education management. In managing an educational institution there must be this system so that all processes that will be carried out/carried out are interconnected with one another. Utilization of this system approach is felt by educational institutions. Here we will discuss the meaning of the system itself, the notion of management and education, what components are in the education system and how the system is in education management and finally about the benefits felt by educational institutions in using this systems approach.